(3efXheI aj eTJHg QLGd GdUMjMjf ddHNGQi heSde ef JbjjO eged hJejjR eTcd ef GdCSeGA hGdcfis - (3eMeO Hf CHj HcQ GdCTNQ , LeGd GdOjf,J (B991 (3g` s ((3RHjO (B_ (3Gdjef s)
(3ChdgG (B:s
(3fMeOc Gddge jG PG GdcQe Ydi LejY SGHZGJ GdfYe s
(3BNQgG (B:s
(3Ke GdUdGI hGdSdGe GdRGci eGUOMJ hQb Ydi GdCQGc Ydi GdfHi GdgGTei CMeOG hGdBd hGdUMH eUGHjM GdgOi s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B1s
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdKGdK YTQs
(3JHUQI GdYfhGf (B:s
(3fXes
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdCOHs